The role of superalloy precipitates on the early stages of oxidation and type II hot corrosion - Potter, Andrew; Sumner, Joy; Nigel, Simms (Cranfield University, 2017)
To meet materials challenges encountered in gas turbines, superalloys have been developed for high temperature, strength, oxidation and corrosion resistance. One strengthening method is using refractory metal additions to form carbide precipitates. However, such precipitates may be detrimental to the alloy’s environmental resistance. This paper reports how refractory metal carbide precipitates affect the early stages of oxidation and hot corrosion of two alloys: Rene 80 (nickel-based) and MarM 509 (cobalt-based). Samples were exposed at 700 °C in either dry synthetic air or 90 ppm SOx, 10·5% CO2, 8·5% O2, 5% H2O (balance N2) with a 80/20 (Na/K)2SO4 deposit (1·5 μg/cm2/hour flux). The oxidation morphology and corrosion products were investigated by scanning electron microscope and energy dispersive X-ray analysis, to show that refractory metal carbide precipitates close to the metal surfaces disrupt protective oxide scale formation, thus providing inward transport routes for corrosive species.
Keywords: Oxidation; hot corrosion; superalloys; MarM 509; Rene 80